2022
DOI: 10.3389/fnut.2022.960763
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and function after high-calorie formula vs. Chinese food intervention in undernourished children with cerebral palsy

Abstract: AimTo investigate the efficacy and safety of high-calorie formula vs. Chinese daily food on the nutritional status and motor function of undernourished children with cerebral palsy (CP).MethodsIn this prospective, assessor-blind, and randomized controlled trial, we recruited children (1–10 years) with CP and undernutrition based on the WHO and the American Society for Parenteral and Enteral Nutrition criteria from the National Children's Medical Center. Participants were randomly allocated (1:1) to a high-calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
0
0
1
Order By: Relevance
“…Overall, these findings support the safety and tolerance of the study ONS intervention (i.e., ONS + DC). The rates of GI tolerance AEs reported in the current study were comparable in type and incidence to those found in other studies investigating ONS in undernourished children ( 86 , 87 ).…”
Section: Discussionsupporting
confidence: 86%
“…Overall, these findings support the safety and tolerance of the study ONS intervention (i.e., ONS + DC). The rates of GI tolerance AEs reported in the current study were comparable in type and incidence to those found in other studies investigating ONS in undernourished children ( 86 , 87 ).…”
Section: Discussionsupporting
confidence: 86%
“…Pemberian intervensi nutrisi dengan memberikan formula tinggi kalori dikatakan aman dan efektif pada anak PS untuk memperbaiki kondisi malnutrisi dan mengalami disfungsi motorik kasar. 15…”
Section: Hasilunclassified